Internal structure of soot particles in a diffusion flame. (January 2019) - Botero, Maria L.; Sheng, Yuan; Akroyd, Jethro; Martin, Jacob; Dreyer, Jochen A.H.; Yang, Wenming; Kraft, Markus
Abstract: The evolution of the internal structure of soot particles was studied in a coflow diffusion flame. Soot particles from the flame were imaged using high resolution transmission electron microscopy. An algorithm to quantify the nano-structure of the particles was extended to study the radial distribution of fringes within the particles. The approximate size of the molecules in the particles was calculated from the fringe lengths, assuming planar peri-condensed PAHs. The molecules are slightly larger (∼16 rings) and more stacked at the core than at the surface (∼12 rings) of the youngest particles sampled, suggesting that the particles could be formed via the stabilisation of a nuclei of larger PAHs and condensation of smaller PAHs on their surface. In the lower-temperature region of the flame the molecules grow mainly at the surface of the particles, whereas the molecules in the core of the particles become less stacked and slightly smaller, indicating some degree of nano-structural mobility. In the higher-temperature region of the flame, a graphitisation process takes place, with the development of a shell of longer (∼20 rings), flatter and more compact molecules, and an immobilised amorphous core. At the tip of the flame the particles are oxidised, mainly through surface oxidation. Graphical abstract: Image 1